Myeloid Wls expression is dispensable for skin wound healing and blood vessel regeneration - Sim, Seen Ling; Blumenthal, Antje; Kaur, Simranpreet; Khosrotehrani, Kiarash (Frontiers in Endocrinology, 2022)
Wnt signaling controls blood vessel growth, regression and patterning during embryonic and postnatal life. Macrophages are major producers of Wnt ligands and angiogenic growth factors. It regulates vascular development and specification during embryogenesis and wound healing. Macrophage dysregulation in wound healing impairs vessel regeneration and delay wound closure. During cutaneous wound healing, the endovascular progenitors (EVPs) proliferate and differentiate into mature endothelial (D) cells in response to signals produced by perivascular cells, including macrophages, governing blood vessels regeneration. However, the role of macrophage’s Wnt production on endothelial cells, especially the EVPs during wound healing is currently unknown. Here we used a cutaneous excisional wound model in mice with conditional deletion of Wnt secretion by myeloid cells (Wlsfl/flLysM-Cre+) to assess the kinetics of endothelial subpopulations (including EVP), myeloid infiltration, collagen deposition and wound closure. Deletion of Wls expression by myeloid cells did not affect wound closure and collagen deposition, indicating that myeloid Wls expression does not promote wound healing and regeneration. Myeloid-specific Wls deletion elevated the EVP population during the peak of angiogenesis, yet without affecting blood vessel density. Wounds in Wlsfl/flLysM-Cre+ animals showed unperturbed myeloid infiltration and differentiation. Overall, our data indicate that macrophage Wnt production shapes EVP kinetics without major relevance to wound healing. These findings extend the knowledge of macrophage and endothelial molecular crosstalk and position myeloid-derived Wnt production as a regulator of endovascular progenitor.